Numerical analysis in rock engineering 1 - Yu, Alford Yat Tung (2014)
Scarcity of useable land space in Singapore has always been a concern. In search for new and innovative ways to create space, government agencies are looking towards underground, creating large caverns for industrial purposes in the near future. In particular, the Jurong Rock Cavern that is expected to be completed in 2014, had been in the spotlight. For a large subterranean cavern, rock reinforcement and support systems have to be adequate and sustainable. Rockbolts have been widely used around the world as part of the rock reinforcement system for underground caverns and mines. With the advent of stronger computing power and better understanding of underground caverns in recent years, numerical analysis has become more popular and reliable which allowed researchers and designers to have a better understanding of the ground underneath. Consequently, more efficient and accurate blueprints can be designed and constructed with higher degree of safety. This report aimed to identify the plausible effects of rockbolts in different rock mass condition, with close reference to Jurong Rock Cavern’s parameters, adopting a discontinuous deformation analysis program to conduct the simulations.